PIROLISIS SEDERHANA LIMBAH PLASTIK DAN IMPLEMENTASINYA SEBAGAI SUMBER BELAJAR BERBASIS EDUCATION FOR SUSTAINABLE DEVELOPMENT (ESD) PADA PEMBELAJARAN KIMIA - Amyyana, Afwu Hayyi; Paristiowati, Maria; Kurniadewi, Fera (LPPM Universitas Negeri Jakarta, 2017)
This study aims to produce a plastic pyrolysis learning resource in the form of books based on Education for Sustainable Development. The development of ESD-based learning resources is done by Borg & Gall (2006) research and development method which is then adjusted into three stages: needs analysis, development stage, and pilot phase. Learning resources produced by reading books on plastic waste issues and handling through a chemical approach, presented with a magazine display, using communicative language, and adapted to chemistry teaching materials class XI SMA of curriculum 2013. Percentage of test results feasibility by material and Language experts is 89.63%, while the results of feasibility tests by media experts amounted to 92.23%, with each reliability of 0.8 and 0.77. The results of ESD-based learning by small-scaled learners are 85% and large scale is 91.44%. Interpretation of assessments of learning resources by experts and learners as a whole has very good criteria for each assessment indicator. Therefore, it can be concluded that the ESD-based learning source developed has been feasible to be used as a reading book to support chemistry learning. Keywords: Plastic Waste, Plastic Pyrolysis, Education for Sustainable Development.